PENGARUH MODEL PEMBELAJARAN DISCOVERY DAN INKUIRI TERBIMBING BERBASIS EKSPERIMEN TERHADAP HASIL BELAJAR FISIKA DAN SIKAP ILMIAH SISWA - Nur Istiqamah; Aris Doyan; Muhammad Taufik (Postgraduate, University of Mataram, 2016)
This research is aimed to investigate the influence of discovery learning model and guided inquiry based experiment method to the physics learning outcomes and students’ scientific attitude. This research is a quasi experiment with 2×2 of factorial design method. The population is all students of 13 classes of grade X of SMAN 2 Mataram. Sample is determined by using a cluster random sampling method. Data is analyzed by t-test statistics of two sample. The results showed that discovery learning model based experiment method has influence to the physics learning outcomes and students’ scientific attitude, and guided inquiry learning model based experiment method has influence to the physics learning outcomes and students’ scientific attitude. Beside that, discovery learning model and guided inquiry based experiment method has influence to the physics learning outcomes and students’ scientific attitude.Keywords: discovery, guided inquiry, experiment, physics learning outcomes, and scientific attitude